Debunking public service? Meta-academic and personal reflections from inside the Swedish Public Service Broadcasting Commission - Snickars, Pelle (MedieKultur: Journal of media and communication research, 2016)
During the last half of 2015, a number of Swedish publishing and broadcasting companies—Bonnier, Schibsted Sweden, Mittmedia, Bauer Group—agreed to fund and establish a national Public Service Broadcasting Commission. The purpose was to initiate a public debate about the behaviour and operation of Swedish public service broadcasters—in particular, how they affected the commercial media market, and generally, to discuss the role of national public service broadcasting in a networked media environment. I was a Commission member, and this article describes the background, debates and proposals put forward by the Commission. On one hand, it focuses the work of the Commission with an emphasis on the different public debates the Commission stirred. On the other hand, the article will in a meta-scholarly fashion elaborate on the academic tradition of doing scholarly work focused on public service in Sweden. A recurrent notion in the article is hence meta-academic. Importantly, the article stresses the scholarly bias in favour of public service that is usually present within this tradition (primarily emanating from the field of political communication). Thus, the article is devoted to various debates surrounding the work of the Commission and the role of academics within these discussions (including myself). Finally, the article presents a few thoughts about what it might mean for academics to be (or become) lobbyists.